2017
DOI: 10.1177/0269216317746571
|View full text |Cite
|
Sign up to set email alerts
|

Needs of people with advanced dementia in their final phase of life: A multi-perspective qualitative study in nursing homes

Abstract: People with advanced dementia in their final phase of life have a multitude of individual and complex needs. This evidence contributes to narrowing the current research gap, offering an orientation framework for research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 36 publications
(48 reference statements)
1
62
0
Order By: Relevance
“…In addition to basic pain medication, movement-specific pain may be reduced by (additional) medication on demand before moving or daily care duties. Regular gentle movement or physiotherapy may help to maintain some mobility and reduce pain (74).…”
Section: Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to basic pain medication, movement-specific pain may be reduced by (additional) medication on demand before moving or daily care duties. Regular gentle movement or physiotherapy may help to maintain some mobility and reduce pain (74).…”
Section: Painmentioning
confidence: 99%
“…Several options are available increasing comfort of food intake comfort for the person with dementia. Health professionals can assist with eating, they can offer preferred food (e.g., sweet) or finger food, and adapt the texture of food (74). To create pleasant environment a focus on the action of feeding and upright position may influence oral food intake positively and reduce risk of aspiration.…”
Section: Eating and Drinking/eating Problemsmentioning
confidence: 99%
“…Perkins et al (105) reported that even persons with advanced dementia were able to engage in spiritual practices that provide life meaning in accordance with their values. Observations in a nursing home showed that some persons expressed a need for religious expression or participating in religious rituals (106).…”
Section: Spiritual and Consoling Care At The End Of Lifementioning
confidence: 99%
“…People with advanced dementia have complex needs [5]. Schmidt et al have investigated the needs in a recent study.…”
Section: Introductionmentioning
confidence: 99%